(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2021)
Background: Elderly people are posing a significant health burden in our country for their multi morbidity as economic growth has increased our life expectancy. Pattern of multi morbidity of this older people varies according to geography, ethnicity, culture and life style. Aim: The aim of this study was to identify the prevalence and pattern of multi morbidity of elderly patients admitted in a tertiary care hospital. Method: 50 random cases of elderly patients aged more than 60 years admitted in medicine and allied wards of Dhaka medical college hospital were observed at this cross-sectional study from January 2017 to June 2017(total 6 months period). Data were reviewed and analyzed using simple frequency and percentage. Protocol was reviewed by institutional ethical board (IRB) of Dhaka medical college hospital. Result: A total number of 50 elderly patients with age ranging from 60 to 95 years were observed with male and female ratio 1.3:1 having multi morbidity among 92.0% patients and female is more affected than male. Hypertension, ischemic heart disease, diabetes mellitus and stroke were found most common diseases as individual. Hypertension and diabetes mellitus was found as the most common multi morbidity pattern followed by hypertension and IHD, stroke & diabetes mellitus. Conclusion: This study sheds light on priority needs of elderly patients in terms of medical facility in tertiary care hospital of Bangladesh. Journal of National Institute of Neurosciences Bangladesh, January 2021, Vol. 7, No. 1, pp. 56-59